DIMISHED POSTURAL CONTROL IS LINKED TO REDUCED NEUROVASCULAR COUPLING DURING THE N-BACK TASK. (16th November 2018) - Jor'dan, A; Manor, B; Iloputaife, I; Bean, J; Lipsitz, L
Abstract: Standing posture, especially under challenging conditions, relies upon the capacity to activate brain regions involved in cognitive-motor function. Our prior work shows that the reduced capacity to regulate cerebral blood flow (CBF) within the middle cerebral artery (MCA) in response to the N-Back executive function task (i.e., neurovascular coupling [NVC]) is linked to worse walking performance in older adults. However, the relationship between NVC and postural control during the N-Back task is unknown. In this proof-of-concept pilot study, 16 young and older adults (22–26 years and 70–84 years, respectively) stood upright and completed the N-Back (i.e., control condition [Identify X, IdX] and an experimental condition [2-Back]) presented on a screen while CBF and postural sway were simultaneously recorded. NVC was quantified by transcranial Doppler ultrasound and defined as the percent change in CBF within the MCA, between the IdX and 2-Back conditions. Postural sway was recorded using a lumbar motion sensor. Elliptical sway area, as well as acceleration and range in the anterior-posterior (AP) and medial-lateral (ML) direction, were computed. Those with lower NVC exhibited greater sway magnitude while performing the 2-Back task (Elliptical area: β=-0.59, p=0.02; AP range: β=-0.68, p=0.005; ML range: β=-0.60, p=0.02), independent of age and BMI. The relationship between NVC and sway during the IdX task trended toward significance, but only for elliptical area (β=-0.56, p=0.05). These results highlight the notion that the ability to regulate postural sway is dependent upon the capacity to increase CBF, especially during challenging tasks, in both younger and older adults.